Evaluation of Some Herbicides for Weed Control in Wheat (Triticum aestivum L.) in Northern Sudan (University of Khartoum Journal of Agricultural Sciences, 2023)
A field trial was conducted at Hudeiba Research Station Farm,River Nile State, Sudan, during 2001/2002, 2002/2003 and 2003/2004winter seasons. The objective was to evaluate the activity and selectivityof three pre-emergence herbicides for weed control in wheat. Theherbicides treatments were pendimethalin (Stomp) at 1.2, 1.8 and 2.4 kga.i. ha-1, oxyfluorfen (Goal) at 0.24, 0.36 and 0.48 kg a.i ha -1 andoxadiazon (Ronstar) at 0.72, 1.08 and 1.44 kg a.i ha -1 . The prevailingweed species in the experimental sites were Ipomoea sp, wild mustard(Sinapis arvensis L.), common beet (Beta vulgaris L.), sweet signal grass[Brachiaria eruciformis (Sm)] and Bermuda grass [Cynodon dactylon (L.)Pers.]. The results showed that the losses in grain yield of wheat, due toweeds competition, were 37%, 29% and 21% for seasons 2001/2002,2002/2003 and 2003/2004, respectively. The herbicide pendimethalin, atall rates tested, showed no phytotoxicity symptoms on wheat. The higherrates of oxadiazon and oxyfluorfen, however, showed slight phytotoxicityto the wheat crop. All herbicide treatments of Ronstar and Goal resultedin good to excellent control (72%–97%) of both grassy and broad-leavedweeds. The herbicide pendimethalin displayed excellent activity againstgrasses and poor to satisfactory activity (0%-67%) against broad-leavedweeds. The weed Cynodon dactylon tolerated all herbicide treatments.With the exception of Stomp, all herbicide treatments significantlyincreased wheat grain yield compared to the weedy check.